Analisis Pengaruh Pertumbuhan Ekonomi, Investasi, dan Belanja Daerah terhadap Ketimpangan Pembangunan Wilayah Provinsi Bali Tahun 2015-2022 - Handayani, Devi Vera; Endang, Endang (Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of economic growth, investment and regional spending on regional development inequality in Bali Province in the 2015-2022 period. Using the Common Effect Model (CEM) with panel data. The results of this research show that economic growth, investment and regional spending do not have a significant effect on development inequality that occurs in Bali Province during the 2015-2022 period.